REMAINING BITS OF ANDRIUS VIŠTELIS’ ARCHIVE - Petreikis, Tomas (Knygotyra, 2016)
Andrius Vištelis (1837–1912), known for having given his wholehearted support to the first Lithuanian periodical publication “Aušra”, left behind a rich creative legacy, which is relatively unscattered. The major part of his personal archive was housed in the Manuscript Repositary of the Lithuanian Literature and Folklore Institute Library. A. Vištelis’ creative process was quite intensive. He took time before destroying handwritten rough drafts manuscripts. At times he failed to release timely publications of his writings and had to postpone his creative endeavours. Due to complicated circumstances related to the survival of his personal archive, not all the documents have survived intact. In the course of time, there have been losses and selective redistributions. From the documents attributed to the most creative period (1879–1889), 35 document files have survived. At the discretion of Adolfa Wysztelewska, A. Vištelis’ wife, her husband’s Lithuanian manuscripts were handed over to the Lithuanian Science Society, whereas the Polish ones remained at her disposal. It has been established that A. Vištelis’ personal archive was compiled in a rather intensive manner. Due to fragmented studies conducted by researchers into the biography of the aušrininkas in question, his archive was not evaluated in its entirety. Among the surviving manuscripts by A.Vištelis, one should mention his letters to “Auszra” editors and his friends in Lithuania Minor. Of special value are the manuscripts of A. Vištelis’ creative activity, including his pieces of poetry, translations and publicistic writings. After a thorough examination of A. Vištelis’ archival documents, the list of his translations and original works has been significantly expanded and suplemented. They reflect both a creative process of his ideas brought to life and the horizon of unrealized ideas. Light has been shed on totally unknown lexicographic endeavours undertaken by A. Vištelis, namely, a compilation of a Greek-Lithuanian dictionary. An interest in the history of the Lithuanian nation and its proper representation served as an impetus for A. Vištelis to conduct genealogical and historical research. He also attempted to write a history of ancient Lithuania. The research conducted provided its author the opportunity to evaluate A. Vištelis’ efforts aimed at preserving the legacy of prominent representatives of writing in Lithuania Minor. In his archival legacy, several previously unknown invoices issued by bookstores and publishing houses have been found, which complemented the history of the library owned by A. Vištelis. He was not a solitary figure in researching the Lithuanian language, therefore the surviving archival documents are most relevant in reconstructing both individual activities carried out by the aušrininkas A. Vištelis, aimed at promoting the Lithuanian identity, and evaluating mutual relationships and accomplishments by the other representatives of national revival who were actively working in A. Vištelis’ surroundings.